Jane Kenyon : The Making of a Poet - Greene, Dana (Book collections on Project MUSE., 2022)
"Pleasure-loving, sarcastic, stubborn, determined, erotic, deeply sad--Jane Kenyon's complexity and contradictions found expression in luminous poems that continue to attract a passionate following. Dana Greene draws on a wealth of personal correspondence and other newly available materials to delve into the origins, achievement, and legacy of Kenyon's poetry and separate the artist's life story from that of her husband, the award-winning poet Donald Hall. Impacted by relatives' depression during her isolated childhood, Kenyon found poetry at college, where writers like Robert Bly encouraged her development. Her graduate school marriage to the middle-aged Hall and subsequent move to New Hampshire had an enormous impact on her life, moods, and creativity. Immersed in poetry, Kenyon wrote about women's lives, nature, death, mystical experiences, and melancholy--becoming, in her own words, an "advocate of the inner life." Her breakthrough in the 1980s brought acclaim as "a born poet" and appearances in the New Yorker and elsewhere. Yet her ongoing success and artistic growth exacerbated strains in her marriage and failed to stave off depressive episodes that sometimes left her non-functional. Refusing to live out the stereotype of the mad woman poet, Kenyon sought treatment and confronted her illness in her work and in public while redoubling her personal dedication to finding pleasure in every fleeting moment. Prestigious fellowships, high-profile events, residencies, and media interviews had propelled her career to new heights when leukemia cut her life short and left her husband the loving but flawed curator of her memory and legacy. Revelatory and insightful, Jane Kenyon offers the first full-length biography of the elusive poet and the unquiet life that shaped her art"--